Bis(diethylamino)pentafluorophenylphosphane as Valuable Precursor for the Design of Tetrafluorophenylphosphanes, Tetrafluorophenylphosphinic and ‐phosphonic Acids. Issue 7 (12th February 2018) - Alter, Christian; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : Facile replacement of the p ‐fluorine atom in bis(diethylamino)pentafluorophenylphosphane [(Et2 N)2 PC6 F5 ] by organolithium derivatives LiR (R = CH3, n ‐Bu, Ph), lithium alkoxides (R = OMe, OEt) and amides (NMe2, NEt2 ) is described. The obtained phosphanes p ‐R‐C6 F4 ‐P(NEt2 )2 are fully characterized. Their acid‐catalyzed hydrolysis affords the corresponding phosphinic acids p ‐R‐C6 F4 ‐P(O)(H)OH, which are smoothly oxidized by treatment with a mixture of DMSO/I2 to phosphonic acids p ‐R‐C6 F4 ‐P(O)(OH)2 . Abstract : Facile replacement of the p ‐fluorine atom in (Et2 N)2 PC6 F5 by organolithium derivatives LiR (R = CH3, n ‐Bu, Ph), lithium alkoxides (R = OMe, OEt), and amides (NMe2, NEt2 ) is described. The acid‐catalyzed hydrolysis of the aminophosphanes affords the corresponding phosphinic acids p ‐R‐C6 F4 ‐P(O)(H)OH, which are smoothly oxidized by treatment with a mixture of DMSO/I2 to phosphonic acids p ‐R‐C6 F4 ‐P(O)(OH)2 .